Judicial control over government’s abuse of authority through administrative and corruption law - Latif, Abdul; Halim, Arivan (Indonesian Journal of Multidisciplinary Science, 2023)
Law Number 30 of 2014 concerning Government Administration, prohibits abuse of authority by government agencies/officials both central and regional, but in practice there are often acts of abuse of authority of Government Agencies/Officials. This paper describes how Judicial Control over abuse of authority through government administrative legal means and Corruption Criminal Acts which, in practice, cause controversy in the enforcement of corruption crimes, especially by Government Officials and State Civil Apparatus. The legal approach to the above problems is carried out by normatively analyzing the laws and regulations governing the prohibition of abuse of power according to Government Administration Law and the Sociology approach according to the practice and / or decision of the Court in the enforcement of corruption crimes committed by organs / bodies of Government officials or State Civil Apparatus. From the results of the study of these problems in the paper, it can be concluded that abuse of authority in government administration is a form of preventive restriction. Meanwhile, abusing authority in the Criminal Law is a form of repressive action. Abuse of authority stipulated in Article 20 of the UUAP is interpreted as an administrative error committed by government agencies/officials, but if there are legal consequences in the form of state financial losses, it is qualified as a criminal act of corruption.